DETERMINING FACTORS PADA KEPUTUSAN PEMBELIAN GADGET PADA MAHASISWA - Syahril Hasan; Jihan Jihan; Tekat Sukomardojo; Endang Fatmawati; Muhammad Hermansyah (Komitmen: Jurnal Ilmiah Manajemen, 2023)
The purpose of this research is to identify the elements of the Surabaya, East Java student environment that contribute to the selection of electronic devices. Product quality, brand reputation, and cost are considered in this study. The study was quantitative in nature, and factor analysis was used to analyze the collected data. Data is gathered through the use of an online survey administered via Google Forms. The population of the city of Surabaya, the focus of this research, is too large to accurately count. A total of 100 persons participated in the study, and all of the hypotheses put to the test were proven correct by the data.